Pemanfaatan Citra Satelit Aqua-MODIS untuk Pemantauan Dinamika Spasio-Temporal Produktivitas Primer Bersih di Perairan Laut Jawa - Alfandy Putra Anugrah; Zainul Hidayah; Abdurrahman As-Syakur; Herlambang Aulia Rachman (Jurnal Kelautan Tropis, 2023)
The Java Sea is an area with the highest rate of exploitation of fishery resources in Indonesia. As much as 32% of the total national fishery production or 2.2 million tons has come from catches in the Java Sea, even though the area of these waters only covers 7% of the total area of national waters. Fisheries productivity is related to the net primary productivity value resulting from the activity of phytoplankton or chlorophyll-a. Net primary productivity (NPP) is influenced by the presence of nutrients, light, chlorophyll-a, Photosynthetically Available Radiation (PAR) and sea surface temperature (SST). The purpose of this research is to analyze the distribution value of net primary productivity in the Java Sea by utilizing Aqua-MODIS satellite imagery using the Vertically Generalized Production Model (VGPM) method with a range of 2017-2021. The results showed that the waters of the Java Sea have quite high fertility and are classified as Eutrophic because the general monthly average from 2017-2021 has an NPP value of >750 mgC/m2/day. The value of primary productivity follows the seasonal pattern, will be high in the east moonson season and decrease in the west monsoon season. Laut Jawa merupakan wilayah dengan laju eksploitasi sumberdaya perikanan tertinggi di Indonesia. Sebanyak 32% dari total produksi perikanan nasional atau sebesar 2,2 juta ton berasal dari hasil tangkapan di Laut Jawa meskipun luas wilayah perairan ini hanya mencakup 7% dari total luas wilayah perairan nasional. Produktivitas perikanan tangkap berhubungan dengan nilai produktivitas primer bersih hasil dari aktivitas fitoplankton atau klorofil-a. Produktivitas primer bersih di suatu perairan dipengaruhi oleh adanya unsur hara, cahaya, klorofil-a, Photosynthetically Available Radiation (PAR) dan suhu permukaan laut (SPL). Tujuan dari penelitian ini adalah untuk menganalisis nilai distribusi produktivitas primer bersih di Laut Jawa dengan memanfaatkan citra satelit Aqua-MODIS menggunakan metode Vertically Generalized Production Model (VGPM) dengan rentang tahun 2017-2021. Hasil penelitian menunjukkan bahwa perairan Laut Jawa memiliki kesuburan yang cukup tinggi dan tergolong Eutrofik karena rata-rata bulanan secara umum mulai dari tahun 2017-2021 memiliki nilai NPP >750 mgC/m2/hari. Nilai produktivitas primer mengikuti pola musim, akan tinggi pada musim timur (kemarau) dan menurun pada musim barat (penghujan).